洋上風況観測のためのドップラーライダー用動揺吸収台とその制御手法の提案 - 片山, 徹; 山本, 裕介; 絹笠, 瑞基; 森田, 万葉 (日本船舶海洋工学会論文集, 2022)
It is necessary to obtain actual wind state at the sea area where offshore wind farm will be constructed to realize its profitability and safety. Our research group has been investigating methods to reduce motion of floating platform caused by wave, wind, current for offshore wind observations by Doppler Lidar, and has proposed a spar-buoy with ring-fin motion stabilizer. However, the spar-buoy is not small, therefore it requires high installation cost. As another method, in this study, a controlled rigid body swing as a motion stabilized platform to place on floating structure is investigated numerically. First, a single pendulum type motion stabilized platform on a spar-buoy type floating plat form with a tension-moored is proposed, and its motion mechanism is clarified. Based on the results, a counter-weight type motion stabilized platform is proposed, which is an improvement of the single pendulum type, and the effectiveness in reducing motion is confirmed. Furthermore, the counter-weight type motion stabilized platform is adjusted so that it has no restoring moment, and further motion reduction is confirmed by using skyhook spring. Finally, it is confirmed that the motion reduction effects are also sufficient when the motion stabilized platform is mounted on a discus-type floating platform.